Program Pengabdian Masyarakat melalui Sosialisasi Perawatan Drainase Lingkungan untuk Pencegahan Banjir di Sedati, Sidoarjo - Dzinnur, Cilda Thesisa Ilmawan; Priambodo, Sebastianus; Haniyah, Haniyah; Atmari, Atmari (Jurnal Pengabdian Masyarakat, 2025)
Flooding is a recurring hydrometeorological problem in low-lying areas such as Sedati District, Sidoarjo, where clogged neighborhood drainage systems often serve as the primary cause of water stagnation. Limited community awareness and participation in routine drainage maintenance further exacerbate this condition. This community service program aims to improve residents’ understanding and skills in maintaining local drainage systems through participatory outreach, while also fostering collective action and community-based flood prevention efforts. The implementation consisted of three stages: (1) Preparation, including field observations and coordination with neighborhood leaders; (2) Implementation, involving interactive outreach through contextual material delivery, discussions, and hands-on demonstrations; and (3) Evaluation, conducted through question-and-answer sessions and feedback questionnaires. The activity, held in RW 02 of Sedatigede Village and attended by 35 residents, resulted in a significant increase in participants’ knowledge of drainage-related issues and maintenance techniques. Furthermore, residents established concrete commitments, including an agreed-upon schedule for routine community clean-ups and the appointment of a drainage monitoring coordinator. Participant feedback indicated 100% satisfaction and expressed strong expectations for program continuity. The findings suggest that participatory outreach is effective in strengthening community capacity and self-reliance in managing local drainage systems. For sustainability, continued mentoring, integration of the program into routine neighborhood agendas, and support from village authorities are recommended.